2019
DOI: 10.1093/neuonc/noz175.082
|View full text |Cite
|
Sign up to set email alerts
|

Actr-40. Phase 2 Safety and Efficacy of Ar-67 (7-T-Butyldimethylsiltyl-10-Hydroxycamptothecin) in Patients With Recurrent Glioblastoma Multiforme (Gbm) or Gliosarcoma

Abstract: BACKGROUND AR-67 (formerly DB-67) is a novel 3rd generation camptothecin with improved safety and lipophilicity than current drugs in this class. Safety and efficacy of AR-67 were evaluated in a Phase 2 study in recurrent GBM/gliosarcoma in adult patients. METHODS AR-67 (7.5 mg/m2) was administered once daily by IV infusion for 5 consecutive days on a 21-day cycle. Cohort 1 patients (N=31/46 enrolled) had not received (or had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In 2010, a phase 2 clinical trial of AR-67 in adults patients with recurrent GBM or gliosarcoma (NCT1124539) was registered. Kumthekar et al [85] reported that among AR-67-treated recurrent GBM patients, the drug appeared to be tolerated well and exhibited a safety profile consistent with or better than currently approved camptothecins. In patients not treated with Bevacizumab, 6/30 patients achieved the primary endpoint of 6-PFS.…”
Section: Dna-targeting Drug Candidates For Gbm Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In 2010, a phase 2 clinical trial of AR-67 in adults patients with recurrent GBM or gliosarcoma (NCT1124539) was registered. Kumthekar et al [85] reported that among AR-67-treated recurrent GBM patients, the drug appeared to be tolerated well and exhibited a safety profile consistent with or better than currently approved camptothecins. In patients not treated with Bevacizumab, 6/30 patients achieved the primary endpoint of 6-PFS.…”
Section: Dna-targeting Drug Candidates For Gbm Therapymentioning
confidence: 99%
“…On the other hand, in patients who failed Bevacizumab treatment, 2/13 of patients achieved a 2-month PFS endpoint. A partial response (PR) was the best overall response in 3/45 treated patients, and stable disease (SD) was the best overall response in 7/45 patients [85].…”
Section: Dna-targeting Drug Candidates For Gbm Therapymentioning
confidence: 99%